2013
DOI: 10.1017/jfm.2013.325
|View full text |Cite
|
Sign up to set email alerts
|

Bounds for Euler from vorticity moments and line divergence

Abstract: The inviscid growth of a range of vorticity moments is compared using Euler calculations of anti-parallel vortices with a new initial condition. The primary goal is to understand the role of nonlinearity in the generation of a new hierarchy of rescaled vorticity moments in Navier-Stokes calculations where the rescaled moments obey D m D m+1 , the reverse of the usual Ω m+1 Ω m Hölder ordering of the original moments. Two temporal phases have been identified for the Euler calculations. In the first phase the 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 14 publications
5
41
0
Order By: Relevance
“…. ; are the vorticity moment integrals (21). Clearly, the divergence of the time integral of any finite-order Ω 2m implies the blowup of R ts 0 kωk ∞ dt, and in our case Ω 4 = O(t s − t) −1 , which fulfills the criterion.…”
Section: Numerical Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…. ; are the vorticity moment integrals (21). Clearly, the divergence of the time integral of any finite-order Ω 2m implies the blowup of R ts 0 kωk ∞ dt, and in our case Ω 4 = O(t s − t) −1 , which fulfills the criterion.…”
Section: Numerical Resultsmentioning
confidence: 58%
“…[11][12][13][14][15][16][17], but in essentially every case, evidence against a singularity was found in subsequent studies (see, for example, refs. [18][19][20][21]. This casts doubt on the validity of the claimed singularity and leaves the question of finite-time blowup an unresolved puzzle.…”
mentioning
confidence: 99%
“…This is the period when this calculation has nearly Euler dynamics and the effects of viscosity compared to nonlinear growth are minimal. The growth of the D m (t) in true Euler dynamics is the topic of another paper (Kerr 2013b). …”
Section: The First Set Of Simulationsmentioning
confidence: 99%
“…Despite some ambiguity in interpreting the initial data used by [38], they managed to advance the solution up to t = 19, which is beyond the singularity time T = 18.7 alleged by [38]. By using newly developed analytic tools based on rescaled vorticity moments, Kerr also confirmed in a very recent study [39] that solutions computed from initial data analogous to that used in [38] eventually converge to superexponential growth and hence are unlikely to lead to a singularity. In a later work, Hou and Li [33] also repeated the computation of [5] and found that the singularity reported by [5] is likely an artifact due to insufficient resolution.…”
Section: Introduction the Celebrated Three-dimensional (3d) Incomprementioning
confidence: 98%
“…Representative work in this direction include [27,45], which studied Euler flows with swirls in axisymmetric geometries, the famous computation of Kerr and his collaborators [38,8,39], which studied Euler flows generated by a pair of perturbed antiparallel vortex tubes, and the viscous simulations of [5], which studied the 3D Navier-Stokes equations using Kida's high-symmetry initial data. Other interesting pieces of work are [10,47], which studied axisymmetric Euler flows with complex initial data and reported singularities in the complex plane.…”
Section: Introduction the Celebrated Three-dimensional (3d) Incomprementioning
confidence: 99%